Understanding Incretin Hormone Action and the Treatment of Diabetes - Vinall, Maria (MD Conference Express, 2012)
In the 44th Claude Bernard Lecture on diabetes, Daniel J. Drucker, MD, University of Toronto, Toronto, Ontario, Canada, discussed his research findings concerning incretin hormone action and the treatment of diabetes. The lecture covered the pharmacological/physiological mechanisms of the glucagon-like peptides GLP-1 and GLP-2, and their relevance to the treatment of human disease.